THE INFLUENCE OF CORPORATE CULTURE, WORK ENVIRONMENT AND JOB SATISFACTION ON EMPLOYEE RETENTION AT PT PUPUK ISKANDAR MUDA - Rafika; Likdanawati; Ibarahim Qamarius; Nurmala (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze and understand the influence of corporate culture, work environment, and job satisfaction on employee retention at PT Pupuk Iskandar Muda. This study uses a quantitative approach with a survey method, with a population of 630 employees of PT Pupuk Iskandar Muda. The sample in this study was 103 employees where the sampling technique used was purposive sampling with the Slovin formula. The independent variables in this study are corporate culture, work environment, and job satisfaction, while the dependent variable is employee retention. Variable measurements use a Likert scale, Data were analyzed using multiple linear regression analysis and hypothesis testing was carried out partially (t-test) and simultaneously, Classical assumption tests such as normality and multicollinearity were also carried out to ensure the validity of the model. The results showed that corporate culture, work environment, and job satisfaction partially and simultaneously have a positive and significant effect on employee retention at PT Pupuk Iskandar Muda, Job satisfaction variables have the greatest influence compared to other variables. Simultaneously, these three variables are able to explain 59.8% of the variation in employee retention, indicating a fairly strong influence.